Supporting Factors and Barriers in Improving the Quality of the Passport Services at the Agam Class I Non-TPI Immigration Office - Nofrianti, Yona; Malau, Hasbullah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study discusses the supporting and hindering factors in optimizing passport issuance services at the Class I Non TPI Agam Immigration Office. The problem arises from the persistence of obstacles despite the implementation of digital innovation through the M-Passport application. This study Applies a descriptive qualitative method, gathering data through interviews and document analysis. The findings reveal that supporting factors include improving service facilities, HR readiness, and ease of digital systems that accelerate service flows. However, a number of inhibitors were also found, such as limited daily quotas, technical problems with the application, and low digital literacy of some people. These findings indicate the need for technical improvements and quota policies, as well as public education so that the implementation of digital passport services can run optimally and inclusively. This study aims to achieve offer concrete recommendations to improve the quality of public services by leveraging information technology.